Perceived Value of Customer Attitude, Knowledge and Consumption of Hatsun Ghee Products in Rasipuram Taluk - Annapoorani. K; Dr. B. Rajendran (IJRDO - Journal of Business Management, 2025)
The prominence of Hatsun Ghee products within Rasipuram Taluk reflects a crucial dimension of the region’s dairy economy serving as a significant factor in building consumer confidence and loyalty. This study investigates how customers perceive, understand and respond to these products by examining their attitudes, levels of awareness as well as depth of product knowledge. Many respondents regard Hatsun Ghee as superior to traditional butter in terms of taste, health value, flavour and overall quality and safety which underscores its growing position in the local marketplace. Frequent consumers display a pronounced sense of exclusivity toward the brand that signals substantial market potential and brand differentiation. Data for this research were gathered through a structured questionnaire administered to 247 participants selected from the study area and a descriptive design was adopted to interpret the findings. The analysis indicates a positive relationship among consumer knowledge, attitude and purchasing frequency suggesting that familiarity with the product enhances both trust and consumption. The study highlights a persistent limitation in public awareness, pointing to the need for more coherent marketing communication and consumer education strategies that could extend the reach and recognition of Hatsun Ghee within the community.